KONSEP PERSAUDARAAN DALAM ‎PANDANGAN ISLAM DAN BUDHA - Arabi, Arianto (Jurnal Ushuluddin, 2020)
The brotherhood in Islam and Buddhism is highly valued, and in other religions as well, brotherhood is seen as a strength in the structure of the religion. Buddhism emphasizes that life can be good and eternal, one of which is through brotherhood. In Islam, on the other hand, brotherhood knows no territorial, geographical, ethnic, racial, or skin color boundaries. One of the most important things in human life on earth is the establishment of strong and harmonious brotherhood. This study aims to understand what is meant by brotherhood and to explore the similarities and differences in the concept of brotherhood in Islam and Buddhism. The results of this study show that brotherhood in Islam represents a way to establish communication on one hand, and on the other hand, it also provides new enthusiasm to practice teachings in accordance with the guidance of the Qur'an and the examples of the Prophets and Messengers. Brotherhood in Buddhist teachings is a part of the happiness of life. Loving-kindness or brotherhood is the desire for the happiness of all beings without exception, often referred to as the pure intention to wish well-being and happiness for others. The essence of brotherhood is the most important part of human life. Brotherhood generates positive energy and motivation, even though in reality, life will not always be orderly, good, and harmonious in the name of brotherhood. As major world religions, Islam and Buddhism have their own unique teachings, believed by their followers based on faith. The universal teachings of Islam and the tolerant teachings of Buddhism are distinct forms that cannot be equated